2013
DOI: 10.3233/jad-130182
|View full text |Cite
|
Sign up to set email alerts
|

Blast Exposure Causes Early and Persistent Aberrant Phospho- and Cleaved-Tau Expression in a Murine Model of Mild Blast-Induced Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) is considered the ‘signature injury’ of combat veterans that have served during the wars in Iraq and Afghanistan. This prevalence of mTBI is due in part to the common exposure to high explosive blasts in combat zones. In addition to the threats of blunt impact trauma caused by flying objects and the head itself being propelled against objects, the primary blast overpressure (BOP) generated by high explosives is capable of injuring the brain. Compared to other means of causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
158
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 50 publications
17
158
0
Order By: Relevance
“…40 Blast injury in humans and experimental animals is associated with increased levels of total and phosphorylated tau protein. 18,[40][41][42] We have previously shown that an increase in levels of tau oligomers results from fluid percussion TBI rats. 21 However, the contribution of tau oligomers to blast TBI has not yet been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…40 Blast injury in humans and experimental animals is associated with increased levels of total and phosphorylated tau protein. 18,[40][41][42] We have previously shown that an increase in levels of tau oligomers results from fluid percussion TBI rats. 21 However, the contribution of tau oligomers to blast TBI has not yet been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] There have been many hypotheses about the causes of this ongoing injury, 14,15 including involvement of tau pathology. [16][17][18][19][20] Recently, we proposed a possible mechanism, based on accumulation and spreading of a toxic form of tau protein, known as tau oligomers. 21 A large body of research has suggested recently that toxicity of tau protein in neurodegenerative disorders, such as Alzheimer's disease (AD), does not depend on the fibrillar aggregates, neurofibrillary tangles, long known to be hallmarks of the disease.…”
mentioning
confidence: 99%
“…10,11,14,21,22 However, even low-level blast pressure waves are transmitted to the brain and exert a variety of biochemical, pathological, and physiological effects in animals, including the induction of chronic behavioral effects. 3,10,14,[21][22][23][24][25][26][27][28][29] Modulation of gene expression mediated by epigenetic changes, such as deoxyribonucleic acid (DNA) methylation, is one way the brain creates new homeostasis in response to experience, including response to injury. 30 Aberrant regulation of gene expression contributes to long-lasting behavioral abnormalities, where epigenetic modifications serve as a regulatory layer decoding environmental signals into sustained changes in gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unfortunately not standard practice. While few researchers have purposely designed experiments to generate scaled-down exposure conditions [14,32,33] against small mammals, others expose animal models to blast parameters relevant to humans [27,[34][35][36][37][38][39][40][41][42][43]. Assuming mass scaling is relevant to bTBI, some of these exposures may effectively result in exposing an animal model to nuclear-sized blasts [29].…”
Section: Scalingmentioning
confidence: 99%